2002
DOI: 10.1021/jf011136z
|View full text |Cite
|
Sign up to set email alerts
|

Composition of a Chemopreventive Proanthocyanidin-Rich Fraction from Cranberry Fruits Responsible for the Inhibition of 12-O-Tetradecanoyl Phorbol-13-acetate (TPA)-Induced Ornithine Decarboxylase (ODC) Activity

Abstract: Phenolics from the American cranberry (Vaccinium macrocarpon) were fractionated into a series of proanthocyanidins and other flavonoid compounds by vacuum chromatography on a hydrophilic, porous polyvinylic gel permeation polymer. Antioxidant activity was not restricted to a particular class of components in the extract but was found in a wide range of the fractions. Significant chemopreventive activity, as indicated by an ornithine decarboxylase assay, was localized in one particular proanthocyanidin-rich fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(67 citation statements)
references
References 31 publications
0
66
1
Order By: Relevance
“…Cranberry extracts containing PACs and other flavonoids reportedly inhibited ODC activity linked to cell proliferation in mouse epithelial (ME-308) cells [33]. Characterization of an active subfraction revealed the presence of dimers and oligomers of catechin/epicatechin, monomeric catechins, and quercetin glycosides.…”
Section: Antiproliferative Activity Of Polyphenolic Extractsmentioning
confidence: 97%
See 1 more Smart Citation
“…Cranberry extracts containing PACs and other flavonoids reportedly inhibited ODC activity linked to cell proliferation in mouse epithelial (ME-308) cells [33]. Characterization of an active subfraction revealed the presence of dimers and oligomers of catechin/epicatechin, monomeric catechins, and quercetin glycosides.…”
Section: Antiproliferative Activity Of Polyphenolic Extractsmentioning
confidence: 97%
“…Several studies of cranberry extracts with anticancer activities implicate the PACs as major contributors [20,33,34].…”
Section: Structure and Activity Of Cranberry Proanthocyanidinsmentioning
confidence: 99%
“…In 2002, a University of Illinois study revealed that extracts of whole cranberry containing PACs and other flavonoids inhibited ODC activity in mouse epithelial (ME-308) cells [45]. A subfraction also inhibited ODC in this cell line.…”
Section: Pacs: Structure and Activitymentioning
confidence: 99%
“…The K þ adduct produced a prominent ion attributed to a 2,5 X 0 cleavage unlike the other two adducts that gave an 3,5 A 2 fragment as the only prominent cross-ring cleavage (Kéki, Deák, & Zsuga, 2001). MALDI-TOF and FAB MS was used by Kandil et al (2002) to identify constituents, including several flavonoid glycosides from an extract of the American cranberry (Vaccinium macrocarpon) that were responsible for the inhibition of 12-O-tetradecanoyl phorbol-13-acetate-induced ornithine decarboxylase activity. Cyanidin 3-dimalonyl glucoside, detected in the aquatic plant hydrilla (Hydrilla verticillata L.f. Royle) by MALDI has not been detected in the surrounding water suggesting that this substance, suspected of being excreted, could be degraded by bacteria (Glomski et al, 2002).…”
Section: Glycosides From Plantsmentioning
confidence: 99%